The Magnetic and Thermally-Induced Spin-Related Transport Features Using Germanene Nanoribbons With Zigzag and Klein Edges - Xu, Gang; Tan, Xingyi; Ren, Dahua (Frontiers in Physics, 2022)
The current work employs the first-principles computations and non-equilibrium Greens function to investigate the magnetic and thermally-induced spin-related transport features using germanene nanoribbons with zigzag and Klein edges (ZKGeNRs). It was demonstrated that the ZKGeNRs with various widths (N) are placed in various spin-resolved electronic states. By increasing the width parameter N from 4 to 9, the ZKGeNRs moves from an indirect-gap bipolar magnetic semiconducting state (BMS) to bipolar spin gapless semiconductor (BSGS), and finally to ferromagnetic metal (FM). Moreover, since the right and the left temperatures of the ZKGeNRs device are different, the spin-up and spin-down currents flow in reverse orientations, demonstrating the spin-dependent Seebeck effect (SDSE). Besides, the threshold temperature decreases as N increases and then disappears, while the spin currents increase as N increases. Simulation results indicated that the ZKGeNRs could be an appropriate choice for spin caloritronic devices and could be utilized in future low-power consumption applications.